PENGARUH INDEKS HARGA SAHAM, RETURN SAHAM, INFLASI, KEBIJAKAN DIVIDEN DAN TINGKAT SUKU BUNGA TERHADAP VOLUME PERDAGANGAN SAHAM PERUSAHAAN. (Studi Empiris pada Perusahaan Indeks LQ45 yang Go Public di BEI Periode 2014-2017). - Aenul Huda; Nur Diana (Universitas Islam Malang, 2019)
ABSTRACTThis Study aims to examine and analyze the effect of stock price index, stock Returns, inflation, dividend policy, and interest rate on the stock trading volume companies index LQ45. This research was conducted at Indonesia Stock Exchange by selecting sample companies listed in Indonesia Stock Exchange in 2014 until 2017. The population in this research as many as 45 companies and the number of samples of 33 companies selected by passing the stage of purposive sampling, so the number of samples of observations for 4 year to 132 samples. The analysis technique used in this research is multiple linear regression. Data analyze in this research using SPSS version 14. The results showed that partially stock trading volume has a significantly effect on the stock price index and inflation. While the stock Returns, dividend policy, and interest rate does not significantly effect the stock trading volume. Together shows that stock price index, stock Returns, inflation, dividend policy, and interest rate significantly on the stock trading volume.Keyword: stock price index, stock Returns, inflation, dividend policy, interest rate, and stock trading volume.